2015
DOI: 10.1038/sc.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical compared with nonsurgical management of fractures in male veterans with chronic spinal cord injury

Abstract: Study design: Retrospective review of a clinical database. Objectives: To examine treatment modalities of incident appendicular fractures in men with chronic SCI and mortality outcomes by treatment modality. Setting: United States Veterans Health Administration Healthcare System. Methods: This was an observational study of 1979 incident fractures that occurred over 6 years among 12 162 male veterans with traumatic SCI of at least 2 years duration from the Veterans Health Administration (VA) Spinal Cord Dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
(39 reference statements)
1
19
1
Order By: Relevance
“…7 A lot of fractures are managed conservatively. 15 But modern surgical techniques allow interventions in this patient cohort as well despite their reduced bone mineral density. However, this study identifies nonunions as a common complication in patients with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…7 A lot of fractures are managed conservatively. 15 But modern surgical techniques allow interventions in this patient cohort as well despite their reduced bone mineral density. However, this study identifies nonunions as a common complication in patients with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a patient chose an amputation after a femur fracture rather than undergo months of traction, whereas another patient who was medically managed developed gangrene requiring an above‐the‐knee amputation 11 . Bethel et al reported 25 LE amputations in 24/44 patients who were operatively managed in a retrospective analysis 34 . Cass reported three above‐the‐knee amputations in nine patients managed nonoperatively 35 .…”
Section: Resultsmentioning
confidence: 99%
“…36 ASIA scores were not uniformly recorded in the time period of the study and thus were not included. Based on our previous work, 37 the development of HO following an incident fracture was exceedingly rare, therefore, we did not examine the association of HO with incident fracture. BMD was not included; it has been reported that low BMD is a predictor of the number of fractures in SCI.…”
Section: Study Limitationsmentioning
confidence: 99%